Building Sustainable Competitive Advantage for Creative Industries: The Role of Human Capital and Intellectual Capital - Dewi Rochmayanti; Nurul Mazidah (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Examining how human capital and intellectual capital drive the competitive advantage of the regional creative industry, this study responds to common constraints that include labor quality, digitalization, and business legality. The main objective is to test the direct influence of human capital on intellectual capital and competitive advantage, as well as assess the mediating role of intellectual capital. A quantitative approach was applied to 140 creative business actors who were purposively selected across subsectors, with standardized measurement and variance-based structural equation modeling analysis. The results show that improving the quality of human capital has a strong effect on strengthening intellectual capital, and intellectual capital has a positive effect on competitive advantage. Human capital also has a direct influence on competitive advantage, although it is smaller than the path through intellectual capital. These findings indicate partial mediation: competitive advantage increases when individual competencies, experience, and training are converted into structured knowledge, documented processes, and strong customer-partner relationships. The value of the power to explain the model is at the medium to high level, confirming the relevance of the research variable. Practical implications include standardization of processes, documentation and digitization of knowledge, strengthening networks, and post-training knowledge sharing rituals. Research limitations include the use of self-assessment data and cross-sectional design; Future studies are suggested to expand the sample, use a mixed approach, and explore long-term dynamics to enrich the understanding of regional competitiveness strengthening policies.